Comparison of Women and Prostitution in Woman at Point Zero and Tuhan Izinkan Aku Menjadi Pelacur - Luzae, Luzae; Setijowati, Adi; Afdholy, Nadya (Anaphora : Journal of Language, Literary, and Cultural Studies, 2023)
Everyone has their rights from birth, but not everyone has the same degree of freedom as everyone else, especially if they belong to a minority group. Because of this, women have always been subject to male power and marginalized in all aspects. Due to disappointment toward the gender differences and objectification, many women fall into a profession that is considered taboo and dishonorable by society, that is as a prostitute. This article focuses on the feminist studies regarding women and how they ultimately choose the path of prostitution at last as experienced by the two main characters, that are Firdaus in Women at Point Zero and Nidah Kirani in Tuhan Izinkan Aku Menjadi Pelacur. This article aims to compare and describe women’s issues related to prostitution in two different countries, which are Egypt and Indonesia. These two countries have the same religious background because both of them have a majority of Muslim population. To complement the research, a comparative literary approach is also employed to identify the similarities and differences to find the factor that determines the female characters to become sex worker. The results indicate that both of the novels tell the life story of a woman who chose to become a prostitute due to their disappointment in man. Despite the similarity, family issues are a significant contributing factor to Firdaus’s becoming a sex worker. As for Nidah Kirani in Tuhan Izinkan Aku Menjadi Pelacur the failure to deal with certain issues effectively. Kirani’s belief in God and the Islamic organization that she thought would show her the real Islam has misled her and because of her disappointment, she turned to be a sex worker.